The Influence Of Service Quality And Facilities On Customer Satisfaction Staying At Hotel Neo Temple Simpang Lima Semarang - Eka Setia Rini; Aleta Dewi Maria (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This study takes the title effect of service quality and facilities on costumers satisfaction at the Neo Candi Hotel Simpang Lima Semarang. The purpose of this study was to analyze the effect of service quality and facilities on customers satisfaction.This research design uses research quantitative methods. The data analysis technique uses analysis of validity, reliability, linear . regression analysis, t test and F,coefficient of determination(R2 )test through the SPSS application. It has a significant effect on customers satisfaction . the result of this study indicate that service quality(X1), facilities(X2), have a significant effect on customer saticfaction(Y).Based on multiple regression test , from the two ciefficient values of the independent variables (Service quality and facilities) that mostinfluence on the dependent variable (costumers satisfaction) is the facilities that is equal to 0.799